The Influences of Career Development, Job Satisfaction, And Organizational Commitment on Employee Turnover Intention (Case Study on The Assistant Level Employees of PT. Bank Negara Indonesia (Persero) Tbk. Regional Office X) - Zagoto, Kartika Hinayasati (International Humanities and Applied Science Journal, 2020)
This study aims to examine and analyze the influences of career development, job satisfaction, and organizational commitment on employee turnover intention on the assistant level employees of PT Bank Negara Indonesia (Persero) Tbk. Regional Office X. This study is quantitative research with a total sample of 86 employees and processed by using SPSS for Windows version 22.0. The probability sampling technique is proportionate random sampling, while the data analysis technique is Multiple Linear Regression. The results show that: career development has a significant influence on turnover intention, job satisfaction does not have a significant influence on turnover intention, organizational commitment has a significant influence on turnover intention, and the F test shows that career development, job satisfaction, and organizational commitment simultaneously have a significant influence on employee turnover intention at the assistant level employees of PT Bank Negara Indonesia (Persero) Tbk. Regional Office X.